Makna Keberlanjutan bagi Petani Rakyat dalam Industri Karet Remah: Studi Kualitatif Kritis di Sumatera Selatan: The Meaning of Sustainability for Smallholder Farmers in the Crumb Rubber Industry: A Critical Qualitative Study in South Sumatra - Hendy Endarwan; Wilfridus B Elu; Tiolina Evi; Gary Putra Etwanto (Jurnal Bisnis dan Ekonomi, 2025)
Abstract : This study examines the discourse of sustainability in Indonesia’s crumb rubber industry through a critical paradigm. Objective : To explore the meaning of sustainability from the perspective of smallholder farmers, analyze the influence of power dynamic within the rubber industry, and identify local forms of resistance against the dominance of corporate sustainability discourse. Methodology : This research employs a qualitative approach using Fairclough’s Critical Discourse Analysis (CDA) method. Data were collected through in-depth interviews, focus group discussions (FGDs), participatory observation, and analysis of policy documents and corporate social responsibility (CSR) reports. The analysis covers three CDA dimensions: text, discursive practice, and social practice. Research Results : The study finds that the sustainability discourse in the crumb rubber industry is dominated by a technocratic paradigm emphasizing efficiency and certification, while smallholder farmers interpret sustainability as livelihood continuity, fair pricing, and economic independence. A counter-narrative emerges in the form of “sustainability from below,” emphasizing social justice and local knowledge. The research highlights the importance of structural transformation through an Inclusive Closed-Loop Supply Chain (ICLSC) model that promotes equity and participation. Keywords : critical sustainability, smallholder farmers, crumb rubber industry, critical paradigm, social discourse, CDA